The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000446190
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Dynamic Observation of the Color Change and Enhancement Effect of Polyethylenimine-Entrapped Gold Nanoparticles Used for Indirect Lymphography

Abstract: Aims: To dynamically observe the color change and enhancement effect of gadolinium-loaded polyethylenimine-entrapped gold nanoparticles (Gd-Au PENPs) as a dual-mode CT/MRI contrast agent for sentinel lymph node (SLN) identification. Methods: In 6 rabbits, Gd-Au PENPs were injected into the right side tongue submucosa, after which the color change of cervical draining lymph nodes was observed. Then the draining lymph nodes were examined by CT/MRI scan. Another 6 rabbits were randomly divided into a CT lymphogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For reviewing the application of CT lymphography in early-stage OSCC, the systematic literature search led to retrieval of 112 PubMed indexed articles for CT lymphography, of which 17 were considered relevant [ 26 , 27 , 28 , 29 , 30 , 31 , 40 , 41 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Of these 17 articles, 11 were animal studies [ 40 , 41 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Cross-reference did not lead to any additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For reviewing the application of CT lymphography in early-stage OSCC, the systematic literature search led to retrieval of 112 PubMed indexed articles for CT lymphography, of which 17 were considered relevant [ 26 , 27 , 28 , 29 , 30 , 31 , 40 , 41 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Of these 17 articles, 11 were animal studies [ 40 , 41 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Cross-reference did not lead to any additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
“…For reviewing the application of CT lymphography in early-stage OSCC, the systematic literature search led to retrieval of 112 PubMed indexed articles for CT lymphography, of which 17 were considered relevant [26][27][28][29][30][31]40,41,[64][65][66][67][68][69][70][71][72]. Of these 17 articles, 11 were animal studies [40,41,[64][65][66][67][68][69][70][71][72].…”
Section: Ct Lymphographymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Au NPs are potentially excellent CT contrast agents for indirect LG imaging to identify SLNs in the head and neck. There have been few studies of indirect LG using Au NPs as CT contrast [ 27 ] and it identified the enhanced SLNs 100% in all rabbits by indirect CT-LG. But it did not have controlled trials with Omnipaque and lymphatic tracer.…”
Section: Introductionmentioning
confidence: 99%